What is the Difference between Cross-National Comparisons and Semi-Comparative Work? Example of Swedish-Ugandan Climate Change Communication Research - Berglez, Peter; Nassanga, Goretti Linda (Journal of Development and Communication Studies, 2015)
This methodological article presents the research approach of semi-comparisons and describes how it could be applied in the field of media and communication studies. The point of departure is that cross-national collaborations do not necessarily always have to result in full-fledged comparative studies, but can “go halfway”, i.e. stay at the semi-comparative level. This is exemplified in terms of an ongoing long-term collaboration between Swedish and Ugandan researchers, focusing on sustainable communication involving the role of media as a provider of relevant information in the case of the climate change issue. The semi-comparative approach – here characterized by: 1) cross-national research connectivity, 2) activities in which one “puts one’s own nation in a wider context” and 3) spontaneous, cross-national research influences – enables the generation of knowledge about the universalism and particularism within the dimensions of mediated climate communication, which would not have been possible with a regular cross-national comparative study.
Keywords: climate change, media, cross-national comparative research, semi-comparative approach, sustainable communication, universalism, particularism.